Function of Protein Kinases in Leaf Senescence of Plants - Yang, Fengbo; Miao, Yuchen; Liu, Yuyue; Botella, Jose R.; Li, Weiqiang; Li, Kun; Song, Chun-Peng (Frontiers in Plant Science, 2022)
Leaf senescence is an evolutionarily acquired process and it is critical for plant fitness. During senescence, macromolecules and nutrients are disassembled and relocated to actively growing organs. Plant leaf senescence process can be triggered by developmental cues and environmental factors, proper regulation of this process is essential to improve crop yield. Protein kinases are enzymes that modify their substrates activities by changing the conformation, stability, and localization of those proteins, to play a crucial role in the leaf senescence process. Impressive progress has been made in understanding the role of different protein kinases in leaf senescence recently. This review focuses on the recent progresses in plant leaf senescence-related kinases. We summarize the current understanding of the function of kinases on senescence signal perception and transduction, to help us better understand how the orderly senescence degeneration process is regulated by kinases, and how the kinase functions in the intricate integration of environmental signals and leaf age information.